SUBKULTUR DAN FAKTOR-FAKTOR BIOGRAFIS MAHASISWA DALAM KEHIDUPAN DI PERGURUAN TINGGI - Indri Astuti (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2020)
This study aims to obtain a picture of the students subculture grouping tendency in viewing the tertiary institutions and value-oriented information service design about tertiary institutions. The method used was a survey of 2 batches in four study programs in a university in Pontianak, namely Guidance and Counseling studies, PG-PAUD, Mandarin Language Education and Sociology Education of FKIP. A total of 224 students from the four study programs of the 2018 and 2019 classes was participated in this study. The results showed that (1) biographically, students had subcultural tendencies starting from politics, then vocational, academic, non-conformist and collegial. (2) the overall student subculture is in the medium category, (3) there are differences in the student subculture between the two batches in viewing tertiary institutions, (4) ADDIE design as a value-oriented information service about tertiary institutions. This study recommends optimizing the role of the Academic Advisor, and (2) the FKIP guidance and counseling service unit and the center for guidance and counseling in carrying out student coaching activities.